Clinical and epidemiological characteristics of acute pancreatitis in high altitude residents - Espinoza-Mayhua, Geraldine (2025)
Introduction: Acute pancreatitis (AP) may have particular characteristics at high altitude that can affect its severity. Objective: To describe the clinical and epidemiological characteristics of AP in residents at high altitude. Methods: Observational and descriptive study conducted in a hospital at 3,250 meters above sea level (masl) in Huancayo, Peru. A total of 129 patients with AP between 2017 and 2021 were included. Clinical, demographic, and management characteristics were analyzed. Data were collected at admission and followed until hospital discharge. Statistical analysis was performed using SPSS version 32, describing qualitative variables with frequencies/percentages and quantitative variables with mean/standard deviation or median/interquartile ranges according to the distribution. Results: The mean age was 45.8 years; 61.2% were women. The mean BMI was 26.1 kg/m², and the hospital stay was 11.1 days. The main cause of AP was biliary (78.3%). The mean SaO2 was 91.6%; PaO2, 68.7 mmHg; PaCO2, 29.4 mmHg; HCO3, 18.8 mEq/L; hemoglobin, 15.5 g; hematocrit, 46.3%; AST, 286.4 U/L; and ALT, 313.9 U/L. The incidence of AP was 38.4 cases per 10,000 admissions. 13.2% were admitted to the ICU, with a mortality rate of 52.9%. The most frequent complications were peri-pancreatic collections (14.7%) and pancreatic necrosis (9.3%). The overall mortality was 13.9%. Conclusion: AP at high altitude shows many similar characteristics to sea level; however, differences in SaO2, PaO2, PaCO2, HCO3, and mortality may suggest an influence of hypobaric hypoxia that should be corroborated in further studies.